Innovation and Creativity in Public Sector - Viera Kozáková (Central European Public Administration Review)
The position of public sector in European countries is significant, especially now when Europe has a goal of smart, inclusive and sustainable growth. The paper examines manners how public sector can contribute to achievement of this goal. The aim of the paper is to investigate the existing modern perspectives on public sector and find out the linkages between them. It deals with the role and importance of intelligence, innovation and creativity in public sector processes. It examines the nature of smart, innovative and creative approach to public sector, their main factors, indicators and variables. The purpose of the paper is to introduce and point out the mentioned approaches that may provide alternatives to previous procedures in public sector. The main findings are based on the main aim of this article, which is to develop a better understanding of innovative, smart and creative approach in public sector with a particular focus on the public involvement.